Storage stability of a-tocopherol extracted from heated and unheated palm oil mesocarp - Mohd. Fauzi, Noor Akhmazillah (Penerbit UTHM, 2010)

(untitled)
a-tocopherol is one ofthe eight vitamers in palm oil which known as powerful biological antioxidants. It is known as phytonutrient which is natural occurring bioactives. However, it has high affinity towards heatand light. An investigation was carried out on the effect of different heating time on the a-tocopherol concentration of the extracted palm oil mesocarp. The work was also aimed to determine the stability of a-tocopherol after stored for three months period. A set of samples were stored at room temperature range between 28T - 32'C. Another set of samples were refrigerated at a temperature between -14'C to - 18'C. The result showed that the highest yield was obtained at 40 minutes of heating with 19.9 ± 0.21% (w/w). Statistical analysis showed that there was a significant difference in a-tocopherol content (p < 0.05) between room and freezer temperature storage. The results also showed that unheated sample records the highest losses' of a-tocopherol with 65.42 ± 3.06% compared to heated sample which is 39.10 ± 1.78%.